Oxford reading tree: Kipper and the giant - Roderick Hunt (Karachi; Oxford University Press, 2012)
The Stage 6 Biff, Chip and Kipper stories provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B involve familiar situations and a variety of fantasy settings through the magic key adventures
Keywords: Readers (Elementary)